Correlating the Interfacial Polar-Phase Structure to the Local Chemistry in Ferroelectric Polymer Nanocomposites by Combined Scanning Probe Microscopy - Jiajie Liang; Shaojie Wang; Zhen Luo; Jing Fu; Jun Hu; Jinliang He; Qi Li (Nano-Micro Letters, 2022)
Highlights A strategy that combines multi-mode scanning probe microscopy-based electrical characterization and nano-infrared spectroscopy is developed. A series of samples with different coupling agents and nanoparticles are characterized to unveil the local structure-property correlation of the interface in ferroelectric polymer nanocomposites. The formation of hydrogen bond between the surface modifiers and the ferroelectric polymer enhances the β-phase content and reduces the domain size of the interface, and hence promotes the local piezoelectric effect and breakdown strength.